Topical treatment for bleeding oncologic wounds in breast cancer patients: a systematic review (Research, Society and Development, 2022)
Objective: To analyze the main clinical evidence about topical treatment for bleeding oncologic wounds in breast cancer patients. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “breast neoplasms”, “breast cancer”, “wounds and injuries”, “malignant fungating wounds”, “malignant wounds” and “bleeding”. Full texts, available in Portuguese, English or Spanish, published between January 2010 and June 2022 were included. In addition to these factors, inclusion criteria were defined as primary studies that investigated treatments, interventions or any topical measures to control bleeding from oncologic wounds in adult patients (≥ 18 years) with breast cancer. Results: 06 articles made up the final sample of this study, with a higher frequency of publication in 2012 (n: 02). Participants in the primary studies reviewed underwent 12 different types of topical treatments, which included hemostatic coatings, non-adherent coatings, vasoactive medication, and cauterizing substances. Overall, all studies reported therapeutic success in relation to the specific forms of treatment employed. Conclusion: Current evidence shows therapeutic success in bleeding oncological wounds from the topical application of several products. However, the results should be interpreted with caution, given the low level of evidence presented by the studies.